Assessment of combining ability and heterosis in bottle gourd (Lagenaria siceraria L.) for yield and attributes character through line × tester design - Singh, R; Sachan, S; Singh , S K; Singh, M; Kumar, M; Kumar, A; Kumar, M; Prakash, S; Singh, B (Plant Science Today, 2025)
General and specific combining ability variance and their effects were studied for thirteen characters in line × tester mating design in bottle gourd. Based on overall per se performance and among the parents, Narendra Dharidar, Punjab Long, and parents Narendra Rashmi were identified as good specific combiners for a maximum of 5 to 6 attributes, including yield for other contributing traits, suggesting that these parents may be used in the hybridization program aimed at the development of superior genotypes/varieties in bottle guard. Tester Arka Bahar and Narendra Madhuri were considered to be good general combiners for 6 to 8 characters. These parents must be utilized in a suitable breeding programme visa-vis selection breeding for improvement productivity of yield and per unit area in bottle gourd. Based on overall results and per se performance, the F1 hybrids, i.e. Pusa Sandesh × Kashi Ganga, IC-321747 × Narendra Madhuri, and NDBG-132 × Narendra Madhuri emerged to be the good specific combiners for maximum traits, including yield, which may be utilized for obtaining transgressive segregants in the next generation. Out of sixty-four cross combinations, only seventeen hybrids revealed superiority over better parents for yield. The seventeen cross combinations that showed more than 24% heterobeltiosis over better parents include: IC-498541×Narendra Madhuri, IC-592210×Arka bahar, Pusa Sandesh×Narendra Madhuri, NDBG-132×Pusa Naveen, Narendra Rashmi×Kashi Ganga, IC-321412×Pusa Naveen, Narendra Rashmi×Arka bahar, Narendra Rashmi×Pusa Naveen, Narendra Dharidar×Narendra Madhuri, Pusa Sandesh×Kashi Ganga, NDBG-132×Arka bahar, NDBG-132×Narendra Madhuri, Punjab long×Narendra Madhuri, Narendra Jyothi×Narendra Madhuri, IC-592210×Arka bahar, IC-338119×Arka bahar and IC- 498541×Kashi Ganga. This suggests that there is a great possibility to produce higher yielding varieties/genotypes.